Surgical-Periodontal aspects in orthodontic traction of palatally displaced canines: a meta-analysis - Cristiano Miranda de Araujo; Pâmela Dias Trannin; Angela Graciela Deliga Schroder; José Stechman-Neto; Bianca L. Cavalcante-Leão; Natanael Henrique Ribeiro Mattos; Bianca Simone Zeigelboim; Rosane Sampaio Santos; Odilon Guariza-Filho (Elsevier, 2020)
The aim was to determine whether there is a difference in the periodontal aspect (gingival recession, probing pocket depth) of the palatally displaced canine (PDC) compared to the contralateral canine. Also, from a surgical perspective, sought to determine whether there is a difference (surgical duration, postoperative pain) between the surgical techniques. The word combinations were adapted for each electronic database: PubMed, LILACS, Scopus, Web of Science, Cochrane Library and gray literature. Studies that met the following criteria were considered eligible: (P) Patients who received orthodontic-surgical treatment for correction of PDC; (I) Performing orthodontic-surgical treatment for traction of the PDC; (C) Comparison of the tractioned canine with its contralateral or between the two techniques; (O) Gingival recession, probing pocket depth, postoperative complications and surgical duration; (S) Randomized and nonrandomized clinical studies or observational studies. The overall prevalence of gingival recession was estimated to be 10.53% [95% CI, 3.87% - 25.59%; I2 = 88%]. No statistically significant difference (p > 0.05) was found between the means of the variables gingival recession, probing pocket depth and surgical duration. The evidence suggests that traction of palatally displaced canines can be considered a reliable and acceptable procedure.